PEREMPUAN PENAMBANG PASIR DAN BATU DI DAERAH ALIRAN SUNGAI GENDOL (QUOVADIS STRATEGI BERTAHAN HIDUP DAN KERUSAKAN LINGKUNGAN DI LERENG MERAPI) - hastuti, Hastuti (UIN Sunan Kudus, 2017)
This research was conducted among sand and stone female miners in Gendol riverbank, Merapi slope, in Sleman regency. It aims at describing women’s social and economical characteristic and their life strategy and also finding the damage of the environment caused by sand and stone mining. The data of this research were collected through focus group discussion and guided in depth interview. Data consist of socio- demographic characteristic, domestic economic problems, life strategy, and their environment knowledge. Data are then analysed using content analysis method. Result shows those women are coming from poor families. Their life strategies are searching various income and limiting family expenses. They aware that sand and stone mining may damage the environment but this is their way to live.